Fabricating superior thermal conductivity SiC–AlN composites from photovoltaic silicon waste. (20th November 2020) - Liu, Weiran; Tian, Jinsai; Xiang, Daoping; Mao, Ruipeng; Wang, Benxue
Abstract: As a result of developments in the photovoltaic industry, more and more photovoltaic silicon waste (PSW) has been generated as a solid contaminant for the environment. This added contamination augments the burden of environmental protection for enterprises and results in the waste of valuable resources. In this research, using PSW as a silicon source, we prepared silicon carbide–aluminium nitride (SiC–AlN) ceramic composites with high thermal conductivity by a two-step method: powder synthesis and ceramic sintering. The powder synthesis process showed that at 1400 °C the Si in the PSW completely reacted with carbon. We also found that SiC–AlN ceramic composites sintered at 1900 °C had optimal thermal conductivity of 124.7 W/m·K. Our study of AlN content on composites suggested that adding 15 wt% AlN to the SiC–AlN ceramic composites resulted in a highest flexural strength of 576.1 MPa. A fracture morphology analysis showed that the main fracture modes of composites gradually changed from intergranular fracturing to transgranular cleavage fracturing as the sintering temperature and AlN content increasing. This novel and clean fabrication of SiC–AlN ceramic composites using PSW as a silicon source provides a sustainable approach of transforming a potentially valuable solid waste into a profitable electronic substrate material. Highlights: Photovoltaic solid waste (PSW) consisted of SiC and Si was used as a silicon source. We prepared SiC–AlN composites with high thermal conductivity by a two-step method. We provided a low-cost way fabricating high thermal conductivity SiC–AlN composites.